The effectiveness of procedure in e-filing among teachers at Sekolah Menengah Kebangsaan Gajah Berang, Malacca / Mysara Syafikah Ishak...[et al] - Ishak, Mysara Syafikah (Faculty of Office Management and Technology, 2012)
Nowadays, online application were popular medium to use in most of sector either government or private. Regarding to achieved the desired of goal Prime Minister to gain the productivity and acknowledgement in ICT, most of the organization implement the system to achieved the goals and objective. The purpose of this research is to examine the effectiveness of e-filing procedure among teachers at SMK Gajah Berang, Malacca towards procedure in e-filing in terms of usability of e-filing, registration, e-payment via FPX and e-filing user guide. Moreover, this study will identify the understanding and familiarity of e-.filing among teachers. The research methodology by using 86 questionnaire method were randomly selected among teachers to know whether the usability and effectiveness of e-filing can influence the application by used of user that their monthly income is above than RM3000. Moreover, based on the finding of this study, the teachers familiar and know exactly the procedures of e-filing that LHDN already implemented to make the ease and faster by using the system and online application. Furthermore, it can see that there has strong significant relationship from this study. In addition, due to completeness of this research, we would provide several of evidence from the expertise of e-filing system to support the need of the LHDN to develop the e-filing system more attractive and interesting to reach the quality and productivity in the desire government sector.